1992
DOI: 10.1002/jmv.1890360112
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to Epstein‐Barr virus and cytomegalovirus in relation to CD4 cell number in human immunodeficiency virus 1 infection

Abstract: Interaction between herpesviruses and human immunodeficiency virus (HIV)1 is postulated in the progression of HIV disease. In order to evaluate the specific antibody responses directed to Epstein-Barr virus (EBV) and cytomegalovirus (CMV) and to provide serological evidence suggesting reactivation of these viruses able to accelerate the immunodeficiency, we studied IgA and IgG titres to EBV and CMV in the serum of HIV positive patients in relation to the CD4 cell number. The titres of IgG antibodies to EBV and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…Overt CMV reactivation was unlikely because CMV IgM responses remained below the detection limit in all samples (data not shown). This is consistent with previous reports about increased or unchanged levels of CMV-specific antibodies during HIV-1 infection 51 52…”
Section: Resultssupporting
confidence: 93%
“…Overt CMV reactivation was unlikely because CMV IgM responses remained below the detection limit in all samples (data not shown). This is consistent with previous reports about increased or unchanged levels of CMV-specific antibodies during HIV-1 infection 51 52…”
Section: Resultssupporting
confidence: 93%
“…(p=00219) showed that the IgAl concentration increased more significantly than the IgA2 concentration (Fig 1). Secretory IgA concentration was 6-07 (2 86) ,ug/ml in the hyper IgA group and 3-25 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) in the normal IgA group (p<0-0001) (Fig 1).…”
Section: Detection Ofiga and Igg Activity To Non-dietary Antigensmentioning
confidence: 89%
“…14 Cytomegalovirus specific IgG antibodies were detected by a commercial antibody capture ELISA (Wellcome Laboratories, Dartford, England). Cytomegalovirus specific IgG seriology was performed by a sandwich type ELISA: briefly, F (ab')2 fragments of goat polyclonal IgG to human a heavy chain (Cappel) were used as solid phase capture reagents.…”
Section: Detection Ofiga and Igg Activity To Non-dietary Antigensmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the difference between latent and lytic antigenspecific immune responses was also observed at the antibody level in HIV-infected subjects, who have decreased titers of EBNA1-but increased titers of viral capsid antigen (VCA)-specific immunoglobulin G (IgG). 61,62 This may indicate that loss of immunity to EBNA1, but not lytic EBV antigens, is a general feature of HIV infection. The question then remains why EBNA1-specific T cells are lost prior to BZLF1-specific T cells.…”
Section: Loss Of Ebna1-specific T Cells In Aids-nhl 3171mentioning
confidence: 99%